Hypertension and its risk factors among college students of Jodhpur, Rajasthan - Balram Meena; Ashok Kumar; Nitin Kumar Joshi; Yogesh Kumar Jain; Mrinalini Mingwal; Pankaj Bhardwaj (Wolters Kluwer Medknow Publications, 2023)
Background: High blood pressure (BP) in adolescents and young adults is a rising concern in today's world. Behavioral factors largely contribute toward the development of hypertension. Once these are established, they often persist throughout life, and if identified timely, might play a significant role in prevalence reduction. This study was conducted to assess the prevalence and association of hypertension and its risk factors in college students of Jodhpur district. Methodology: A cross-sectional study was conducted in ten colleges across five zones of Jodhpur district using modified WHO STEPS questionnaire and by taking physical measurements of BP, height, and weight. Descriptive analysis was done using means and percentages, and statistical significance was established using prevalence odds ratio (POR). Results: Of the 421 study participants, 251 (59.60%) were males and 170 (40.20%) were females, with a mean age of 20.12. The prevalence of risk factors and significant association were observed between gender and educational level with behavioral habits. Further, hypertension prevalence (16.15%) was found to be associated with smoking (POR = 2.72), high salt intake (POR = 3.21), physical activity (POR = 0.30), overweight (POR = 2.34), and obese body mass index (POR = 4.02). Conclusion: The study provided evidence of high prevalence of hypertension and its associated behavioral risk factors such as tobacco, salt, and physical inactivity. Such evidences may be utilized for health promotion programs for the specific age group and region.